2009
DOI: 10.1007/s11010-009-0127-0
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin domain receptor 2 is associated with the increased expression of matrix metalloproteinase-13 in synovial fibroblasts of rheumatoid arthritis

Abstract: Regulation of matrix metalloproteinase-13 (MMP-13) by collagen matrix in the synovial fibroblasts of rheumatoid arthritis (RA) is critical event in the progressive joint destruction. Our previous study indicated that a collagen receptor, discoidin receptor 2 (DDR2), was highly expressed in the synovial fibroblasts of RA. However, the functional role of DDR2 in the regulation of MMP-13 production in synovial fibroblasts has not been elucidated. In this study, we initially demonstrated that the DDR2 and MMP-13 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 35 publications
5
52
0
Order By: Relevance
“…Previously, we and others demonstrated that collagen II-DDR2-MMP-13 axis may contribute to articular cartilage destruction in arthritis [14,21]. These observations collectively suggest that Cbl-b abundance may impact DDR2-related pathogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Previously, we and others demonstrated that collagen II-DDR2-MMP-13 axis may contribute to articular cartilage destruction in arthritis [14,21]. These observations collectively suggest that Cbl-b abundance may impact DDR2-related pathogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Over the past decade, different groups have identified several target genes downstream of DDR2 activation in various types of cells, including distinct MMPs, interlukin 6 (IL-6), and IL-12. (22,25,(27)(28)(29)(30)54,55) However, the detailed signaling pathways mediating DDR2 regulation of target-gene transcription remain ill-understood. Our study on DDR2 modulation of osteoblastic and chondroblastic gene expression enriches the target-gene list of DDR2.…”
Section: Discussionmentioning
confidence: 99%
“…The constitutively activated Ddr2 plasmid pSecTag2B-FcDDR2 was described previously. (30) The pCMV5-Runx2 was provided by professor Gerard Karsenty (Baylor University Medical School, Waco, TX, USA). Runx2 S301, 319E and Runx2 S301, 319A mutants were generated by polymerase chain reaction (PCR) and inserted into pcDNA3.1 vector (Invitrogen, Carlsbad, CA, USA).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, DDR1 has been proposed to interact with several cofactors, including ShcA, Nck2, and Shp-2 (14,15), and STAT5, NF-B, and p38 MAPK (5,16,17). DDR2 appears to require the recruitment of Src for complete phosphorylation (5,18,19) and has been shown to signal through the ERK1/2 MAPK and activator protein (AP)-1 (20,21). However, detailed studies on the pathways activated by DDR 1 and 2 in different cell types and their transcriptional targets have not yet been described.…”
Section: Discoidin Domain Receptors (Ddrs)mentioning
confidence: 99%